2001
DOI: 10.1042/ba20000091
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and immunological properties of human cardiac troponin I fragments

Abstract: Cardiac troponin I (cTnI) is the inhibitory subunit of the troponin complex and is a biochemical marker for myocardial infarction (MI). It is found in human serum within 4-6 h following MI. One of us has shown [Morjana (1998) Biotechnol. Appl. Biochem. 28, 105-111] that MI patient serum TnI is cleaved at the N- and C-terminals and that the TnI fragments exist as a complex with tropinin C (TnC) and troponin T (TnT). In the present study, we have generated C-terminal truncated TnI fragments and studied their imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Accordingly, peptides containing the two cysteine residues were observed at masses that indicate alkylation by 2-mercaptoethanol, as noted previously for the intact protein. Two peptides were observed with molecular masses that correspond to fragments [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and with an additional 563 u. If their assignment is correct, these peptides verify the presence of the expression tag on the N-terminus of this recombinant protein.…”
Section: Analysis Of Recombinant Proteinsmentioning
confidence: 95%
See 2 more Smart Citations
“…Accordingly, peptides containing the two cysteine residues were observed at masses that indicate alkylation by 2-mercaptoethanol, as noted previously for the intact protein. Two peptides were observed with molecular masses that correspond to fragments [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and with an additional 563 u. If their assignment is correct, these peptides verify the presence of the expression tag on the N-terminus of this recombinant protein.…”
Section: Analysis Of Recombinant Proteinsmentioning
confidence: 95%
“…One peptide observed with a molecular mass of 1975.8 Ϯ 1 could be assigned as fragment [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], whose calculated molecular mass of 1976.1 includes acetylation on the Nterminus. No peptides were observed at a mass corresponding to [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] without acetylation. Peptides were observed at molecular masses that agreed well with the calculated molecular masses of peptides and [1-39], with both peptides being N-acetylated and containing two phosphate groups.…”
Section: Analysis Of Extracted Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of low concentrations of GuHCl could stabilize the molten globule state of apomyoglobin and cytochrome c [13]. GuHCl-induced stabilization of protein is also seen with disulfide isomerase [14], suggesting that chaotropic agents at lower concentrations can stabilize the partially folded intermediates though they behave as potent denaturants at higher concentrations. Further, it has been shown that n-alkyl sulfates also stabilize intermediate states in the folding/unfolding pathway of cytochrome c [15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…It is well documented that cTnI is prone to degradation and binding to plastic and glass surfaces. 15,16 Therefore, the dilution linearity was analysed by determining the cTnI concentration of spiked specimens with a clinically applied, two-step chemiluminescence immunoassay, which is distributed by ARCHITECT under the brand name STAT Troponin-I. In the rst step, cTnI binds to antibody-coated paramagnetic microparticles.…”
mentioning
confidence: 99%